Time and cost management on project development in it sector - KUMAR, DR. P. PRAVEEN; MS. KEERTHANA. A.R. (The journal of contemporary issues in business and government, 2020)
The main purpose to conduct this study is to know how to implement time management and cost reduction while doing a project. Also to understand the perception of employees in the IT industry about cost reduction and time management practises. This is an empirical study. Descriptive research methodology is used in the study as the research design and sampling method used is convenience sampling. The size of the sample collected in this study is 77 and primary data is used. The responses are collected from IT employees. The software supported to interpret and analyse the data is IBM SPSS software which is widely used for finding many quantitative solutions. The tools used for the study are frequency analysis, mean analysis and ANOVA to analyse the data. The results of this research were found to be cost management helps to eliminate unnecessary cost elements.